Genome constitution and differentiation of subgenomes in Siberian and Far Eastern endemic species of the genus Elymus (Poaceae) according to the sequencing of the nuclear gene waxy - A. V. Agafonov; S. V. Asbaganov; E. V. Shabanova (Kobozeva); I. V. Morozov; A. A. Bondar (Вавиловский журнал генетики и селекции)
Fifty-three species of perennial grasses in the genus Elymus L. (Poaceae), which are widespread in Russia, are generally assumed to have three haplome combinations: StH, StY and StHY. The StH-genome species, endemic to Russia, remain the least studied. R. Mason-Gamer and co-authors have previously shown in a series of studies that a molecular phylogenetic analysis of the low-copy gene waxy (GBSS1) sequences significantly complements cytogenetic data on the genomic constitution and evolutionary relationships among both North American and Asian species of the genus Elymus. To determine the species’ genomic constitution and to evaluate the level of phylogenetic differentiation, we examined the GBSS1 gene in 18 species of Elymus from Siberia and the Russian Far East, including the fol- lowing 14 endemics: E. charkeviczii, E. jacutensis, E. kamczadalorum, E. komarovii, E. kronokensis, E. lenensis, E. macrourus, E. margaritae, E. subfibrosus, E. sajanensis, E. transbaicalensis, E. peschkovae, E. uralensis, and E. viridiglumis.PCR amplification products of GBSS1 gene fragments (including exons 9–14) were cloned and 6–8 clones per accession were sequenced. It appears that all the species studied have St and H subgenomic gene variations. The most significant differences between the subgenomic variants St and H were found in intron 13. The H subgenome contains a 21-bp-long deletion in intron 13 in all Elymus genotypes, probably derived from a common ancestor of the H and P genomes. Instead of this deletion, all St subgenomes have a relatively conservative sequence similar to that of the genus Pseudoroegneria, whose ancestor is considered to be the donor of the modern St subgenome for all Elymus species. Cluster phylogenetic analysis revealed differentiation in St and H subgenome sequences into two evolutionary variants: St1 vs. St2 and H1 vs. H2, respectively. Variants of the St and H subgenomes were found homologous to various modern species of the ancestral genera Pseudoroegneria and Hordeum: St1 to P. strigosa, St2 to P. spicata, H1 to H. jubatum, and H2 to H. californicum. The details of the relationships between Russian and North American species of the genus, as well as a number of microevolutionary interconnections in the group of boreal endemic species of Siberia and the Russian Far East were revealed. The new results obtained here are essential for the development of a phylogenetically oriented taxonomic system for the genus Elymus.